Synthesis and Spectral Studies of Some Heterocyclic Azetidione Compounds - Patel, R.P.; Parikh, K.S. (Asian Journal of Chemistry, 2010)
Some new heterocyclic azetidiones have been prepared by the reaction of various Schiff bases with chloro acetyl chloride. The intermediate Schiff bases were synthesized by the condensation of isoniazid with various aldehydes. The structures of compounds have been confirmed by elemental analysis and spectral analysis.